2009
DOI: 10.1080/09553000802641151
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological evaluation and correlation with the local effect model (LEM) of carbon ion radiation therapy and temozolomide in glioblastoma cell lines

Abstract: High LET carbon ion irradiation is significantly more effective for glioblastoma cell lines compared to photon irradiation. An additional treatment with TMZ may offer a great chance especially for several tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 41 publications
7
52
0
Order By: Relevance
“…We do not understand why Friedrich et al claim that our Figure 1 should intriguingly suggest an equivalence between the a and b values from Suzuki et al (2000) and Combs et al (2009) and the values derived from the new model. Differences in the LQ parameters which Friedrich et al noted between the linear quadratic (LQ) parameters published in the original experimental papers (Suzuki et al 2000, Combs et al 2009) and the K iDSB and K cDSB values we reported in Table I and Figure 5 of Mairani et al (2013a) can be mostly explained by the fact that we factored in the non-uniform uncertainties of the experimental data points in our fits.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…We do not understand why Friedrich et al claim that our Figure 1 should intriguingly suggest an equivalence between the a and b values from Suzuki et al (2000) and Combs et al (2009) and the values derived from the new model. Differences in the LQ parameters which Friedrich et al noted between the linear quadratic (LQ) parameters published in the original experimental papers (Suzuki et al 2000, Combs et al 2009) and the K iDSB and K cDSB values we reported in Table I and Figure 5 of Mairani et al (2013a) can be mostly explained by the fact that we factored in the non-uniform uncertainties of the experimental data points in our fits.…”
mentioning
confidence: 83%
“…Differences in the LQ parameters which Friedrich et al noted between the linear quadratic (LQ) parameters published in the original experimental papers (Suzuki et al 2000, Combs et al 2009) and the K iDSB and K cDSB values we reported in Table I and Figure 5 of Mairani et al (2013a) can be mostly explained by the fact that we factored in the non-uniform uncertainties of the experimental data points in our fits. Details of the fitting procedure were not discussed in our original publication as they are, as we will show, not of principal concern for demonstrating the validity of the proposed model, and particularly in view of the initial modelling stage and rough accuracy which we claimed in our publication for high LET radiation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…To calculate the dose rate given to cell nuclei, the following formula adapted from Belli et al (1989) and Combs et al (2009) was used:…”
Section: Dosimetry: Linear Energy Transfer Calculations Beam Homogenmentioning
confidence: 99%
“…Despite gross tumor resection or debulking, postoperative radiation therapy and chemotherapeutic treatment, most of the patients died in two years (Laperriere et al 2002;Combs et al 2009). Nevertheless, radiotherapy is still one of the most important methods for GBM (WHO IV) (Legler et al 1999;Bache et al 2011).…”
mentioning
confidence: 99%